La “Buona morte” in scena. Due casi di εὐθανασία a confronto: Augusto (Suet. Aug. 98-99) e Tullio Marcellino (Sen. epist. 77) - Spurio Venarucci, Ivan (Lucius Annaeus Seneca, 2023)
This article analyses the analogies between two εὐθανασία scenes: that of Augustus (Suet. Aug. 98-99) and that of Tullius Marcellinus (Sen. epist. 77). I argue that the official version of Augustus’ death, as it emerges from Suetonius, is the paradigm lying behind Seneca’s depiction of Marcellinus’ suicide. Despite killing himself, Lucilius’ friend stages an exitus facilis, i.e. an εὐθανασία, which shares many traits with the death of Augustus (peacefulness, pleasure, lack of pain, nobleness, life as a comedy and death as the final act). Through the exemplum of Marcellinus, Seneca offers a death paradigm which is both “august” and private (i.e. apolitical), in opposition to the trendy Stoic political suicide.